Tracking the hackers. - Baylon, Caroline (World Today)
The article looks at the hacking of Sony Pictures Entertainment Inc. which attracted controversy on the entertainment company's film "The Interview." The attribution of the cyberattack to Pyongyang, North Korea because of the country's objection to the film and based on the evidence presented by the Federal Bureau of Investigation (FBI) is discussed. The author believes that trusting the FBI is difficult because of its intelligence mistakes and failure to provide details about the evidence.